Coffee in health and disease prevention - Preedy, Victor R.; Abramovic, Helena (Academic Press, 2015)
Coffee in Health and Disease Prevention presents a comprehensive look at the compounds in coffee, their reported benefits (or toxicity risks) and also explores them on a health-condition specific level, providing researchers and academics with a single-volume resource to help in identifying potential treatment uses. No other book on the market considers all the varieties of coffee in one volume, or takes the disease-focused approach that will assist in directing further research and studies. The book embraces a holistic approach and effectively investigates coffee and its specific compounds.